FAKTOR EKSTERNAL DAN INTERNAL DALAM UPAYA PENGEMBANGAN AGRIBISNIS PADI ORGANIK - Inda Ilma Ifada; Gt. Khairun Ni'mah (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
Organic Rice Farming has disadvantages in marketing. Most organic rice farmers to sell their crops to traders and surrounding communities a place to stay at a price not much different from non-organic rice. During this organic rice sold in supermarkets comes from the island of Java, they can not sell to supermarkets because of limited capital. This study aims to identify the internal and external factors as organic rice agribusiness development efforts in South Kalimantan long-term goals give an idea to the public / investor on opportunities for organic rice farming that development of organic rice farming in South Kalimantan increased. The method used by purposive sampling and accidental sampling. Sample total 76 peoples. The result showed the strength of organic rice farming is the resulting product is beneficial to health. The main drawback is the limited capital. The biggest opportunity in terms of increasing farmers for fertilizer production technology and biological pesticides. The biggest threat that farmers have difficulty obtaining and maintaining organic certification. Keywords: Organic rice, External factors, Internal factors, Agribusiness